PENGARUH ETIKA KERJA ISLAM, KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI KJKS BMT LOGAM MULIA GROBOGAN - Sodiq, Amirus (BISNIS, 2018)
This research aims to determine the effect of Islamic work ethics, transformational leadership and work motivation on employee performance, this research was conducted using a quantitative approach with multiple linear regression analysis, where previously classical assumptions were tested, namely normality test, heteroscedasticity test, autocorrelation test and multicollinearity test, the results of multiple linear regression analysis concluded that Partially Islamic Work Ethics (X1) have no significant effect on employee performance, Transformational Leadership (X2) has a significant effect on employee performance, and partially Work motivation (X3) has a significant effect on employee performance